Expression profile of the entire family of Adhesion G protein-coupled receptors in mouse and rat - Ebendal Ted (BMC Neuroscience, 2008)
Abstract Background The Adhesion G protein-coupled receptors (GPCRs) are membrane-bound receptors with long N termini. This family has 33 members in humans. Several Adhesion GPCRs are known to have important physiological functions in CNS development and immune system response mediated by large cell surface ligands. However, the majority of Adhesion GPCRs are still poorly studied orphans with unknown functions. Results In this study we performed the extensive tissue localization analysis of the entire Adhesion GPCR family in rat and mouse. By applying the quantitative real-time PCR technique we have produced comparable expression profile for each of the members in the Adhesion family. The results are compared with literature data and data from the Allen Brain Atlas project. Our results suggest that the majority of the Adhesion GPCRs are either expressed in the CNS or ubiquitously. In addition the Adhesion GPCRs from the same phylogenetic group have either predominant CNS or peripheral expression, although each of their expression profile is unique. Conclusion Our findings indicate that many of Adhesion GPCRs are expressed, and most probably, have function in CNS. The related Adhesion GPCRs are well conserved in their structure and interestingly have considerable overlap in their expression profiles, suggesting similarities among the physiological roles for members within many of the phylogenetically related clusters.